Evaluation, Gap Analysis, and Potential Expansion of the Finnish Marine Protected Area Network - Virtanen, Elina A.; Viitasalo, Markku; Lappalainen, Juho; Moilanen, Atte (Frontiers in Marine Science, 2018)
Marine Protected Areas (MPAs) are considered to be an essential tool for safeguarding marine biodiversity. Sustainable use of the oceans and seas relies on the benefits of MPAs, now even more than ever, due to environmental degradation and anthropogenic impacts on marine ecosystems. Various international and regional agreements require that nations designate sufficiently marine areas under protection. MPAs are powerful tools, if coherent and ecologically efficient. Assessing the functionality of MPA networks is challenging, unless extensive data on underwater species and habitats is available. We evaluated the efficiency of the Finnish MPA network by utilizing a unique new dataset of ~140 000 samples, collected by the Finnish Inventory Programme for the Underwater Marine Environment VELMU. For the evaluation of MPAs, we used comprehensive data on: species distribution and abundance models for over 100 taxa, IUCN Red List of Ecosystems, fish reproduction areas, EU Habitats Directive Annex I Habitats and human pressures. Using the quantitative conservation planning and spatial prioritization method Zonation, we identified sites of high biodiversity and developed a balanced ranking of underwater conservation values. Only 27 % of the ecologically most valuable features were covered by the current MPA network. Based on the analyses a set of expansion sites were identified, complementing the ecological and geographical gaps in the current MPA network. Increasing the protected sea area by just one percent with the selection of the most valuable areas indicated by the analysis, the protection level of biological features could be significantly increased. We also discovered that the EU Directive habitats are not in their present form functional proxies for marine benthic species. This suggests that MPA networks based on habitats are not sufficient for safeguarding marine biodiversity in the northern Baltic Sea. Furthermore, the produced rankings are essentially environmental value maps, they can be used in ecosystem-based marine spatial planning and impact avoidance, including, e.g., siting of wind energy or aquaculture. Our approach and analytical procedure can be replicated elsewhere in the Baltic Sea and in other marine areas around the world, provided sufficient data exists.